Consumption of the edible sea urchin Mesocentrotus nudus attenuates body weight gain and hepatic lipid accumulation in mice. (August 2018) - Yamamoto, Ryoko; Minami, Hisanori; Matsusaki, Hiromi; Sakashita, Mami; Morita, Naoki; Nishimiya, Osamu; Tsutsumi, Naonobu; Hosokawa, Masashi; Itabashi, Yutaka; Matsui, Toshiro; Ura, Kazuhiro
Graphical abstract: Highlights: Sea urchin intake resulted in reduced body, liver, and visceral fat weights in mice. Sea urchin intake reduced plasma aspartate aminotransferase and alanine aminotransferase levels in mice. Sea urchin intake resulted in reduced hepatic triacylglycerol levels in mice. Sea urchin intake had no effect on cholesterol levels in mice. Sea urchin intake induced uncoupling protein-1 in brown adipose tissue in high-fat diet fed mice. Abstract: The beneficial health effects of edible sea urchin consumption in mice fed a normal (ND) or high-fat diet (HFD) were investigated in this study. Notably, sea urchin-administered (250, 500, 1000 mg/kg) mice exhibited lower body, liver, and visceral fat weights, lower plasma levels of aspartate aminotransferase and alanine aminotransferase, and lower hepatic triacylglycerol levels than those fed carboxymethyl cellulose (CMC). Despite the high levels of cholesterol found in sea urchins, intake of these organisms had no effect on plasma cholesterol levels among the mice tested. Additionally, sea urchin consumption resulted in enhanced levels of arachidonic acid and docosahexaenoic acid within mouse livers. Lastly, mice fed HFD with sea urchin (500 mg/kg) exhibited increased mRNA expression of uncoupling protein-1 within brown adipose tissue, compared with those fed HFD with CMC. In conclusion, consumption of sea urchin might provide a protective effect against the development of obesity and/or nonalcoholic fatty liver disease.